2020
DOI: 10.1515/nanoph-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and high-efficiency accelerating beam generation by dielectric catenary metasurfaces

Abstract: AbstractSelf-accelerating beams show considerable captivating phenomena and applications owing to their transverse acceleration, diffraction-free and self-healing properties in free space. Metasurfaces consisting of dielectric or metallic subwavelength structures attract enormous attention to acquire self-accelerating beams, owing to their extraordinary capabilities in the arbitrary control of electromagnetic waves. However, because the self-accelerating beam generator possesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…The energy efficiency is limited for several reasons. First, owing to the fabrication defects, the measured diffraction efficiency of the fabricated metasurface is only ~30% (Section 6 of the Supplementary file), which can be further improved by optimizing the fabrication process and adopting semicontinuous metasurfaces 20 , 53 . Second, since the intensity is spread over a sort of V-shape with a cusp, the amount of energy focused on the specific spot of interest is ~16.3%.…”
Section: Resultsmentioning
confidence: 99%
“…The energy efficiency is limited for several reasons. First, owing to the fabrication defects, the measured diffraction efficiency of the fabricated metasurface is only ~30% (Section 6 of the Supplementary file), which can be further improved by optimizing the fabrication process and adopting semicontinuous metasurfaces 20 , 53 . Second, since the intensity is spread over a sort of V-shape with a cusp, the amount of energy focused on the specific spot of interest is ~16.3%.…”
Section: Resultsmentioning
confidence: 99%
“…Selecting the design of meta-atoms depends on a phase modulating mechanism which affects the phase and phase dispersion at each position (Shrestha et al, 2018;Chen et al, 2019d). Applying spatial multiplexing (Lin et al, 2016;Li et al, 2017;Arbabi et al, 2016c), cascading (McClung et al, 2020), or catenary (Pu et al, 2015;Zhang et al, 2020b), metasurfaces are widely used methods for achromatic focusing, and combining computational imaging with flat optics (Colburn et al, 2018) is also adopted for broadband phase modulating. Several metalenses that exploit resonance on dielectric (Aieta et al, 2015;Arbabi et al, 2017;Chen et al, 2018aChen et al, , 2018cWang et al, 2018) or plasmonic (Hu et al, 2016;Wang et al, 2017a;Hsiao et al, 2018) meta-atoms have been demonstrated.…”
Section: Aberration Correctionmentioning
confidence: 99%
“…Especially, asymmetric photonic spin-orbit interactions, enabled by the combination of the geometric phase and propagation phase, have shown great potential to achieve multifunctional devices and systems [ 7 , 8 ]. Different from the traditional metasurface that spatially tailors the geometries of the scatters to introduce the phase discontinuities [ 9 ], a quasi-continuous metasurface does not rely on numerous elaborately arranged elements to fulfill various functionalities [ 10 , 11 , 12 ]. A quasi-continuous metasurface beam splitter divides one laser beam into multiple beams and can be applied in structured light [ 13 , 14 , 15 , 16 ], optical interconnects [ 17 ], and camera calibration [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%